The Effect of Use Ivermectin on Strongylus infection in Awassi of Sheep males (Journal of Hama University, 2024)
This work was carried out on Awassi of sheep male (1-2) years old in Agricultural Scientific Research Center in Hama, in order to identify the effect of using Ivermectin on Strongylus infection. For this purpose, Ivermectin was injected subcutaneously with dose (1) ml per (50) kg weight during specific time intervals, for a groups similar in age, feeding, conditions and general health status under the semi-intensive breeding system.The group of males were divided into four groups, in each (10) animals,  the first group (the control) was not given any anti-parasitic, while The second was injected with ivermectin once during two months, and the third was injected with ivermectin 3 times at an interval of 20 days between one dose and the other for two months, while the fourth group was injected with ivermectin (twice) every 30 days, once for two consecutive months. and the groups continued to be monitored during the experiment period (70 day).Laboratory results of flotation test and Mc-Master tests showed a prevalence of Strongylus infection about (81.13)% in the heard of male sheep studied by exame the dung samples and calculated a number of oocytes in (1) g of dung (EBG). Small  decrease in the infection was observed after injecting ivermectin in a single dose only in the (2) group compared to the(4) group that was injected every (30) days  which infection intensity appear clear decreased. while the(3) group that was injected every (20) days achieved a big decrease in the of infection compared with the other groups and the control group.The results of statistical analysis (ANOVA) showed clear significance (P < 0.05) during the injection for one time only compared to the control group, and very clear of significance (P < 0.000) when injecting ivermectin (20, 30) day, therefore ,the research is recommended to use the Ivermectin compound against Strongylus infection because its apparent effectiveness ,despite the uninterrupted chain of infection under the semi-intensive culture system.As the study showed prevent  (90%-80%) in order of infection for third and fourth group compared control group despite of stope throw out  oocytes  in study time